Implementation of Work Competency Certificates (WCC) for Fisherman Gas Station Construction Project Workers at PT. XYZ - Devi Ellynovia; Nur Cahyadi (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2024)
In the era of globalization and intense competition in the construction sector, having a Work Competency Certificate (WCC) is crucial for project workers to meet established work safety and skill standards. This research aims to explore the causes of not having a Work Competency Certificate (WCC) by construction workers and the solution to this problem in the Fuel Filling Station for Fishermen (SPBU Nelayan) project. Qualitative descriptive methods were used in this research by collecting data through field observations, interviews and documentation. Research findings reveal that the main barriers to obtaining WCC include mismatching educational levels, lack of understanding of the importance of WCC, and lack of relevant work experience. The strategies adopted to overcome this problem include training for employee development, increasing awareness about the benefits of WCC, and implementing effective human resource management to support employee professional growth and improve work safety standards. The results of this research emphasize the importance of overcoming barriers to obtaining WCC and implementing holistic strategies in improving employee qualifications, which in turn provides benefits in the form of competitive advantage and increased job security standards.